Effectiveness of Using Latch Score as Breastfeeding Assessment and Early Preparation for Breastfeeding - Mahardika, Putri; Azzahra, Hanifa (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2023)
Mothers whose babies have problems and are cared for separately make mothers feel less confident about breastfeeding because they think about the health of their babies. Lack of confidence in breastfeeding is a factor in the failure to breastfeed. An instrument is needed to assess the breastfeeding process as a nurse's initial step to establish nursing interventions in nursing mothers. Objective: Apply the use of the LATCH instrument as an initial assessment of breastfeeding so that it can assist nurses in arranging nursing interventions. Methods: case study with implementation based on Evidence Based Nursing Practice: LATCH SCORE was applied to three nursing mothers in two hospital. Results: four breastfeeding mothers were assessed by LATCH SCORE and then intervention was carried out in the form of education and counseling for breastfeeding mothers. Conclusion: This intervention is very effective in assessing position and attachment during breastfeeding, thus helping nurses to tailor interventions according to the needs of the mother. Suggestion: it is hoped that the maternity nurse can carry out a LATCH Score assessment to assist in the assessment and arrange interventions according to the needs of nursing mothers.